Circumcision by CO2 laser 10600nm - Amjed Saeed Yaqob; Ali Fouad Rashid Al-Khazraji; Mardukh Sami Abd (Iraqi Journal of Laser, 2025)
Background: Male Circumcision is one of the most common surgical procedures performed in children. The indications for circumcision differ from country to country and might include both medical and religious ones.  Several different surgical procedures for circumcision have been documented, with various results and complications.Aim of study: to evaluate the safety, effectiveness of the use of CO2 laser in circumcision and asses any possible post-operative complication(s).Patients, Materials & Methods:  A prospective study was done for 26 patients who were circumcised by using a CO2 laser at 10600 nm from PLATIN, using continuous wave (CW) power that is set at  6 W with different exposure times during the period from June to August 2022. The patients had been operated under local anesthesia. In all cases, the parents had requested circumcision for religious reasons. The patients were followed up for 14 days, and reported having one or more complications postoperatively (if any).Results: The patients were grouped into three age groups based on their age: the first group was 6–12 months old, the second group was 13–24 months old, and the final group was 25–36 months old, with a mean age of 14.7 ± 8.7 months. All patients had a single-session operation. Twenty patients (76.92%) had moderate pain, four patients (15.38%) had mild pain, and two patients (7.7%) had severe pain. Twenty patients (76.92%) had no bleeding; six patients (23.07%) had bleeding and were treated conservatively. Twenty-four patients (92.3%) had no infection, and only two patients (7.7%) developed a simple surgical site wound infection. Regarding the edema, four patients (15.4%) suffers of null degree: 12 patients (46.2%) of 1st degree: 8 patients (30.8%) of 2nd degree; and 2 patients (7.6%) of 3rd degree after four hours; while 17 patients (65.4%) suffers of null degree; 5 patients (19.2%) of 1st degree; 3 patients (11.5%) of 2nd  degree; and 1 patient (3.9%) of 3rd degree after 7 days. 18 patients (69.2%) were completely satisfied. The operative time is less than that of conventional methods. All the patients were discharged after half an hour.Conclusion: A CO2 laser circumcision is a safe and effective procedure, and the device is very beneficial due to precise results with decreased pain, infection, bleeding, and edema following surgery.